Neurocognitive Insights into Child Sexual Abuse Perpetrators: Understanding Cognitive and Emotional Profiles: A Case-Control Study - Mohsen Daneshvari; Mohammad Nami; Arsalan Ashrafi; Sayyed Hamid Najibi; Roohollah Zahedian Nasb; Ebrahim Moghimi Sarani (Iranian Journal of Medical Sciences)
Background: Child sexual abuse (CSA) is one of the most sensitive crimes in the world. Some perpetrators of CSA suffer from paraphilic disorders, including pedophilia (PE). This research is designed and implemented with the aim of neurocognitive evaluation of CSA perpetrators.Methods: A case-control study was conducted over a period of 6 months from October 2022 to the end of March 2023 in Shiraz, Iran on the Experimental group (EG) (CSA perpetrators) (n=12) and the Control group (CG) (n=13). During these evaluations, information was obtained about sexual orientation, history of sexual activity, cognitive distortions, and cognitive performance of both groups. Physiological arousal factors were also measured using a polygraph device while participants viewed half-naked digital paintings of immature and adult individuals. Additionally, the study utilized functional near-infrared spectroscopy to measure hemodynamic changes in the left frontal pole (Fp1) and the right frontal pole (Fp2) while participants performed the Stroop task (ST). Results: Compared to CG, EG showed a greater tendency towards homosexuality in the past (P=0.017), present (P=0.019), and ideal (P=0.022). Using the mini-mental state examination, cognitive distortion was shown more common in the EG group (P=0.001). Additionally, there was a significant relationship between sexual abuse between the ages of 12 and 16 and committing a crime (P=0.041). Cognitive performance during ST was poorer in EG than CG. Moreover, in the statistical comparison between groups, the amount of oxyhemoglobin (HbO) and deoxyhemoglobin (HbR) was significantly different in areas Fp1 (HbO: P=0.006 and HbR: P=0.014) and Fp2 (HbO: P=0.008 and HbR: P=0.005). Based on polygraph data, EG exhibited less emotional control than CG when viewing half-nude images of children (skin conductance: P<0.001 and heart rate: P=0.004).Conclusion: Based on the results of this study, the CSA perpetrators seem to have a poorer neurocognitive function than the control group.